PENGEMBANGAN MODUL PEMBELAJARAN SISTEM BAHAN BAKAR ˜BENSIN DI SMK MUHAMMADIYAH 1 BAMBANGLIPURO BANTUL: Pengembangan Modul Pembelajar Sistem Bahan Bakar Bensin di SMK Muhammadiyah 1 Bambanglipuro Bantul - Martiyan Wisnu Pratomo; Rabiman Rabiman; Arif Bintoro Johan (JURNAL VOKASI DEWANTARA (JVD), 2022)
This research aims to: (1) develop the Carburetor Gasoline Fuel System module; (2) find out the feasibility of the module in Engine Maintenance and Components subject at eleventh grade students of Technical Light Vehicle at SMK Muhammadiyah 1 Bambanglipuro. In conducting this research, the researcher used an educational research and develop (R&D) method. The researcher developed a learning media of the Engine Maintenance Module and Its Components of the Carburetor Gasoline Fuel System using the modified Four-D method by Thiagarajan and Semmel. The stages used in the module development process were the define stage, the design stage, the develop stage and the disseminate stage. The feasibility data collection used questionnaire and observation. To get the assessment and response of module feasability, this research also involved material expert, media expert, the teacher and the students. The descriptive analysis is used’as the data analysis technique. The results howed hat he process of developing the Carburetor Gasoline Fuel System module was based on the define stage, the design stage, the development stage and the disseminate stage. The results of the module feasibility level assessment conducted by material expert obtained 85% eligibility level with a very feasible category. According to media expert, the feasibility level was 81.03% with a very’decent category. Meanwhile, the influential teacher gained 80.20% with a very decent category. The students’ response was 80.80% with a very’decent category. In conclusion, the Carburetor Gasoline Fuel System module is appropriate and able to help the learning process at SMK Muhammadiyah 1 Bambanglipuro.